Legal Reconstruction of Digital Asset Confiscation of Cybercrime in Indonesia - P Pebrin Putra Yasa (Sabtida, 2026)
This article examines the legal framework for the enforcement of digital assets in cybercrime within the Indonesian legal system. The rapid development of digital assets, particularly cryptocurrencies such as Bitcoin and Ethereum, has created new challenges for criminal law enforcement, particularly in asset recovery mechanisms. Existing regulations, including the Criminal Code (KUHP) and the ITE Law, do not comprehensively address the unique characteristics of blockchain-based assets. This study employs a normative juridical method with legal, contextual, and comparative approaches. The findings reveal significant legal and technical barriers to tracking, freezing, and identifying digital assets due to their decentralized and anonymous nature. This article proposes a reconstruction of criminal law policy by recognizing digital assets as objects of potential harm, strengthening procedural mechanisms, and enhancing international cooperation. This study contributes to the development of cyber law and provides practical recommendations for law enforcement agencies in Indonesia.